KLF14 activates the JNK-signaling pathway to induce S-phase arrest in cervical cancer cells - Du, Ying; Ye, Hui; Lin, Mei; Cao, Lili (Frontiers in Immunology, 2023)
Objective To explore the role of Krüppel-like factor 14 (KLF14) and its underlying mechanism(s) of action in cell-cycle regulation in cervical cancer. Methods:Lentiviral infection was used to construct KLF14, KLF14 zinc-finger structural mutations, and empty vector controls in SiHa and HeLa cervical cancer cells. The effect of KLF14 on cervical cancer cell cycle was detected by flow cytometry. The effect of KLF14 on the expression of cyclin-dependent kinase 2 (CDK2), cyclin A2 (CCNA2), and MAPK signalling pathway-related molecules was detected by fluorescence quantitative RT-PCR (qRT-PCR) and western blot. Cervical cancer cells were treated with JNK-pathway inhibitors/agonists before we assessed changes in the cell cycle and the expression of the CDK2, CCNA2, and p-JNK/JNK. Subcutaneous xenograft studies to explore the effects of KLF14 on cervical cancer cell proliferation in vivo, and western blotting was implemented to measure the expression of CCNA2, CDK2, and the activation levels of the MAPK-signaling pathway proteins in tumours. Conclusions: KLF14 induced S-phase arrest in cervical cancer cells and inhibited the proliferation of cervical cancer cells in vivo; the induction of S-phase arrest was related to its zinc-finger structure. KLF14 also activated the JNK pathway to induce S-phase arrest and promote the expression of CDK2 and CCNA2.